PMCNA_RS00975 activates NF-κB and ERK1/2 through TLR2 and contributes to the virulence of Pasteurella multocida - Xu, Tenglin; Kou, Mingxing; Cao, Peili; Liu, Benjin; Zheng, Yating; Jiang, Qian; Liu, Jiasen; Kang, Hongtao; Yang, Mingfa; Guo, Dongchun; Qu, Liandong (Frontiers in Cellular and Infection Microbiology, 2024)
IntroductionPasteurella multocida is a pathogenic bacterium known to cause hemorrhagic septicemia and pneumonia in poultry. Reports have indicated that certain proteins, either directly involved in or regulating iron metabolism, are important virulence factors of P. multocida. Therefore, understanding virulent factors and analyzing the role of pro-inflammatory cytokines can help us elucidate the underlying pathogenesis.MethodsIn this study, the PMCNA_RS00975 protein, a putative encapsuling protein encoded by a gene from a specific prophage island of the pathogenic strain C48-1 of P. multocida, was investigated. To further explore the impact of the PMCNA_RS00975 protein on pathogenicity, a PMCNA_RS00975 gene mutant of P. multocida strain C48-1 was constructed using positive selection technology. Subcellular localization was performed to determine the location of the PMCNA_RS00975 protein within P. multocida. The recombinant protein PMCNA_RS00975 of P. multocida was soluble expressed, purified, and its role in pro-inflammatory cytokines was investigated.ResultsThe mutant exhibited significantly reduced pathogenicity in the mice model. Furthermore, subcellular localization indicated that the PMCNA_RS00975 protein was located at the outer membrane and expressed during infection of P. multocida. Additionally, our experiments revealed that recombinant PMCNA_RS00975 protein promotes the secretion of the IL-6 pro-inflammatory cytokines triggered by the TLR2 receptor via NF-κB and ERK1/2 signaling pathways in the macrophages.DiscussionThis study identified a novel virulence factor in the C48-1 strain, providing a basis for understanding the pathogenesis and directions for the development of attenuated vaccines against P. multocida.